Review of the requirements for effective mass casualty preparedness for trauma systems. A disaster waiting to happen?. (February 2022) - Gabbe, Belinda J.; Veitch, William; Mather, Anne; Curtis, Kate; Holland, Andrew J.A.; Gomez, David; Civil, Ian; Nathens, Avery; Fitzgerald, Mark; Martin, Kate; Teague, Warwick J.; Joseph, Anthony
Summary: Mass casualty incidents (MCIs) are diverse, unpredictable, and increasing in frequency, but preparation is possible and necessary. The nature of MCIs requires a trauma response but also requires effective and tested disaster preparedness planning. From an international perspective, the aims of this narrative review are to describe the key components necessary for optimisation of trauma system preparedness for MCIs, whether trauma systems and centres meet these components and areas for improvement of trauma system response. Many of the principles necessary for response to MCIs are embedded in trauma system design and trauma centre function. These include robust communication networks, established triage systems, and capacity to secure centres from threats to safety and quality of care. However, evidence from the current literature indicates the need to strengthen trauma system preparedness for MCIs through greater trauma leader representation at all levels of disaster preparedness planning, enhanced training of staff and simulated disaster training, expanded surge capacity planning, improved staff management and support during the MCI and in the post-disaster recovery phase, clear provision for the treatment of paediatric patients in disaster plans, and diversified and pre-agreed systems for essential supplies and services continuity. Mass casualty preparedness is a complex, iterative process that requires an integrated, multidisciplinary, and tiered approach. Through effective preparedness planning, trauma systems should be well-placed to deliver an optimal response when faced with MCIs.